Leader self-development: an emerging strategy for building leadership capacity - Simmons, Mathias J. (Kansas State University, 2017)
Leader self-development is being pushed by organizations today as a practical and cost-efficient strategy to develop leadership skills. However, the research on leader self-development is still sparse and there are questions that should be answered before much stock can be placed in self-development as a viable means to increase leadership capacity. This research attempts to address these questions in several ways. First, the first study outlines a theory and process to create a scale that measures the quality of self-development activities that leaders engage in. Furthermore, a nomological network is examined with dispositional constructs that were and were not be related to the quality of leader self-development activities. The results from these scale development efforts were generally positive with the exception of the challenge dimension of quality. Second, the second study builds on previous literature by examining the interactive effect of leader self-development quality and quantity in predicting leader effectiveness and finds that quality appears to play the more important role. Finally, the second study also addresses the lack of research examining situational factors that may affect leader self-development quality. This study found that transformational leadership was related to the quality of leader self-development activities and that quality mediated the relationship between transformational leadership and effectiveness. Overall, this research addresses several gaps in the leader self-development literature and creates a foundation for future research to build on.
Keywords: Leader self-development